2013
DOI: 10.1111/joms.12062
|View full text |Cite
|
Sign up to set email alerts
|

Passion Isn't Always a Good Thing: Examining Entrepreneurs' Network Centrality and Financial Performance with a Dualistic Model of Passion

Abstract: We propose a conceptual model that links entrepreneurs' passion, network centrality, and financial performance, and test this model with small business managers in formal business networking groups. Drawing on the dualistic model of passion, we explore the relationships that harmonious and obsessive passion have with financial performance, mediated by network centrality. Results indicate that harmoniously passionate entrepreneurs had higher out‐degree centrality in their networking group (i.e., they were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
200
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 187 publications
(209 citation statements)
references
References 99 publications
(180 reference statements)
1
200
1
7
Order By: Relevance
“…Furthermore, most studies that included performance as an outcome variable have found that the relationship between passion and performance is mediated by either the goals set, the persistence, engagement, or deliberation to meet these goals, and the experiences that follows the passion (Bonneville-Roussy et al, 2011;Ho & Pollack, 2014;Ho et al, 2011;Li, 2010;Vallerand et al, 2008;Vallerand et al, 2007). In the present context passion for work represents the general work attitude, whereas engagement and workaholism represent a cognitive state and behavior, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Furthermore, most studies that included performance as an outcome variable have found that the relationship between passion and performance is mediated by either the goals set, the persistence, engagement, or deliberation to meet these goals, and the experiences that follows the passion (Bonneville-Roussy et al, 2011;Ho & Pollack, 2014;Ho et al, 2011;Li, 2010;Vallerand et al, 2008;Vallerand et al, 2007). In the present context passion for work represents the general work attitude, whereas engagement and workaholism represent a cognitive state and behavior, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…It has also previously demonstrated satisfactory reliability on both scales with alphas ranging from .83 -.89 (HP) and . 74 -.88 (OP;Forest et al, 2011;Ho & Pollack, 2014;Houlfort, Philippe, Vallerand, & Ménard, 2014). HP was measured by items such as "My work is well integrated in my life," and OP was measured by items such as "My work is the only thing that really turns me on.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations